Comparative transcriptomics and proteomics analysis of the symbiotic germination of Paphiopedilum barbigerum with Epulorhiza sp. FQXY019 - Tian, Fan; Wang, Juncai; Ding, Fangjun; Wang, Lianhui; Yang, Yanbing; Bai, Xinxiang; Tan, Chengjiang; Liao, Xiaofeng (Frontiers in Microbiology, 2024)
Paphiopedilum barbigerum is currently the rarest and most endangered species of orchids in China and has significant ornamental value. The mature seeds of P. barbigerum are difficult to germinate owing to the absence of an endosperm and are highly dependent on mycorrhizal fungi for germination and subsequent development.However, little is known about the regulation mechanisms of symbiosis and symbiotic germination of P. barbigerum seeds. Herein, transcriptomics and proteomics were used to explore the changes in the P. barbigerum seeds after inoculation with (FQXY019 treatment group) or without (control group) Epulorhiza sp. FQXY019 at 90 days after germination. Transcriptome sequencing revealed that a total of 10,961 differentially expressed genes (DEGs; 2,599 upregulated and 8,402 downregulated) were identified in the control and FQXY019 treatment groups. These DEGs were mainly involved in carbohydrate, fatty acid, and amino acid metabolism. Furthermore, the expression levels of candidate DEGs related to nodulin, Ca 2+ signaling, and plant lectins were significantly affected in P. barbigerum in the FQXY019 treatment groups. Subsequently, tandem mass tag-based quantitative proteomics was performed to recognize the differentially expressed proteins (DEPs), and a total of 537 DEPs (220 upregulated and 317 downregulated) were identified that were enriched in processes including photosynthesis, photosynthesis-antenna proteins, and fatty acid biosynthesis and metabolism. This study provides novel insight on the mechanisms underlying the in vitro seed germination and protocorm development of P. barbigerum by using a compatible fungal symbiont and will benefit the reintroduction and mycorrhizal symbiotic germination of endangered orchids.